PENERAPAN MODEL PEMBELAJARAN TREFFINGER TERHADAP HASIL BELAJAR GEOGRAFI PESERTA DIDIK FASE E SMA NEGERI 7 KERINCI - sonia, Sonia Lorensa; Slamet Rianto; Ade Irma Suryani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the low creativity and learning outcomes of students, which were below the Minimum Learning Achievement Criteria. This was due to students' lack of participation in learning activities such as asking questions, giving feedback, engaging in discussions, and reading independently. The purpose of this research was to examine the application of the Treffinger learning model on the geography learning outcomes of Phase E students at SMA Negeri 7 Kerinci. This research employed a quasi-experimental method with a Pretest-Posttest Control Group Design. Random sampling was used, with class X E5 as the experimental group and X E1 as the control group. The findings revealed that the creativity score in the experimental group was 75.50% (categorized as good), higher than the control group's 68.57%. The t-test showed a significant difference (p=0.000<0.05), indicating that Treffinger learning had a significant impact. The average posttest score increased from 78.75 to 82.97 after using the Treffinger model, demonstrating its effectiveness in improving learning outcomes.